ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KREDIT KONSUMTIF (STUDI KASUS BANK UMUM DI INDONESIA) - Nofriadi Nofriadi; Syamsul Amar B (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to determine the effect of credit interest rates  and Gross Domestic Products on consumer credit demand at commercial banks in Indonesia. The type of data in this study is time series. In analyzing coherent data from 2010 to 2018, multiple regression methods were used. Based on the results of testing (1) credit interest rates do not significantly influence consumer demand for loans at commercial banks in Indonesia. (2) Gross Domestic Product has a significant effect on consumer demand for loans at Commercial Banks in Indonesia.